A reescrita de textos nas 7ª e 8ª séries do ensino fundamental : caracterização de aspectos linguístico-discursivos - Moterani, Natalia Gonçalves (2012)
This research takes into consideration the written as work, involving revision and rewritten process, departing from the objectives of delimitating and characterizing the linguistic and discursive aspects that constitute these stages, considering the different levels of textual production done in Elementary School. So, in order to comprehend this process, we analyze 198 textual productions, executed by 7th and 8th grades, involving public and private schools. Accordingly, it has as aim the setting up of the written characteristics of these levels and the aspects delimitation which are revised by the teacher in the moment of the texts revision and correction produced in classroom, by means of data collection about what is answered and comprehended in the texts rewritten, made by the students. In this context, the work is guided in the Bakhtin Circle enunciative theory and in the written conceptions, approached by Fiad and Mayrink-sabinson (1994) and Sercundes (2001) e in the Menegassi (1998) and, mainly, Ruiz (2010) approaches about revision and rewrite. As regards the kinds of notes held in the revision, our analysis distinguish of Ruiz (2010) research, expanding its discussions and revealing that the methods of intervention made by the teachers of the 7th and 8th grades are configured differently than the author proposes. With respect to the rewritten, the tables and the examples of the linguistic and discursive aspects answered show that the act of adding is the most executed, following the replace, the suppress and displace, the latter being not very accomplished in the rewriting of these series. From these analyzes, we build worksheets that point the linguistic and discursive aspects of the revision and the rewritten process. This way, we shared them into answered and comprehended ones, actions that, respectively, depart of the revision and are made by the student autonomously, without the teachers' intervention.